The Oxford companion to the Supreme Court of the United States - Hall, Kermit (Oxford University Press, 2005)
Includes entries on key cases and full treatment of crucial areas of constitutional law, such as abortion, freedom of religion, school desegregation, freedom of speech, voting rights, military tribunals, and the rights of the accused. Essential for judges, lawyers, academics, journalists.